THE DEVELOPMENT OF HUMAN RESOURCES FOR STATE CIVIL APPARATUS WITH THE CORPORATE UNIVERSITY SDGs SYSTEM - Agung, Bayu Nugraha (DIA: Jurnal Administrasi Publik, 2024)
CorpuS Jatim is a policy taken by the Provincial Government of East Java in developing the human resources of the state civil apparatus with the concept of Corporate University SDGs. The CorpuS East Java policy has been in effect since 2021 and the main implementer is the East Java Provincial Human Resource Development Agency. This study aims to analyze the success of the implementation of human resource development for civil servants with the Corporate University SDGs system within the East Java Provincial Government using the Theory of Implementation Success according to G. Edward III which consists of Communication, Disposition, Resources and Organizational Structure. In this study using qualitative-descriptive research methods and data collection techniques through interviews, observation and documentation. The results of the study show that the implementation of human resource development for the state civil apparatus with the Corporate University SDGs system within the East Java Provincial Government has been successfully implemented. However, in practice there are several obstacles that become inhibiting factors in the implementation of human resource development programs. The inhibiting factors found in this study were the lack of disposition and delivery of information related to the implementation of activity events in developing the human resources of the state civil apparatus with the Corporate University SDGs system within the East Java Provincial Government.